The Effect Of Metformin On Clinical And Metabolic Outcomes In Women With Polycystic Ovary Syndrome: A Systematic Review And Meta-Analysis (The Review of Diabetic Studies, 2025)
Background: Polycystic ovary syndrome (PCOS) is a prevalent endocrine-metabolic disorder among women of reproductive age, characterized by hyperandrogenism, menstrual irregularity, and insulin resistance. Metformin, an insulin-sensitizing agent, is widely used to address metabolic, reproductive, and cardiovascular dysfunctions associated with PCOS. This systematic review and meta-analysis evaluated the clinical and metabolic effects of metformin across randomized controlled trials and comparative studies.Methods: Twelve peer-reviewed studies were systematically analyzed following PRISMA 2020 guidelines. Eligible studies included randomized trials and cohort studies examining the effects of metformin, alone or in combination with other interventions, on metabolic (BMI, insulin resistance, lipid profile) and reproductive (ovulation, menstrual regularity, androgen levels) outcomes in women with PCOS.Results: Metformin consistently improved fasting insulin, HOMA-IR, and serum testosterone levels, with moderate reductions in BMI and waist circumference. Combination regimens, such as metformin with semaglutide or oral contraceptives, yielded superior improvements in metabolic control and menstrual regularity. Cardiovascular risk markers and endothelial function also improved significantly. However, response variability across phenotypes was observed.Conclusions: Metformin demonstrates robust efficacy in enhancing metabolic and reproductive health in women with PCOS. Its combination with adjunct therapies further optimizes clinical outcomes, particularly among obese or insulin-resistant subgroups. Personalized treatment based on phenotype and metabolic profile may enhance therapeutic precision and long-term benefits.